Car rental hub / Muhammad Shahreen Aqiff Mat Ayob - Mat Ayob, Muhammad Shahreen Aqiff (2020)
Car Rental Hub is a prototype of a car rental booking system for UiTM Kuala Terengganu where students can make car rental booking via the system. Car Rental Hub is developed by using e-marketplace business model where it acts as the hub to connect students and car rental owners. It is proposed as a new way for the students to book a car for rental. Initially, the students have trouble to make a booking as there are no system to make a booking. The students must contact each of the car rental owner to check on the availability of the car before making a booking. The owner also was having trouble to record the booking of the students as it was kept in a logbook. Double booking problems happened often. With the presence of Car Rental Hub, the booking process can be done easier and faster. This is because the booking process can be done via the system. This prototype system was developed using Adapted Waterfall Model where it includes six sequential stages. The stages are requirement analysis, design, implementation, testing and documentation phase. A test case has been set up according to three scenarios to make sure the functionality of the system is approved. A set of questionnaires involving ten questions based on system usability scale (SUS) questions. The questionnaire has been distributed to the users that test the system to measure the level of usability of Car Rental Hub. The feedback and comments gained from the testing process will be taken into consideration for future enhancement of the system. Based on the system usability scale scoring system, Car Rental Hub scored 92.5 which by SUS standards, it can be considered a good system if the score is more than 68. This concludes that the users that tested the system were satisfied with Car Rental Hub. It is hoped that Car Rental Hub will enhance the current business process for the students, car rental owners and for Kolej Kerawang staffs.